AN ECONOMIC ANALYSIS OF WHEAT PRODUCTION IN THE LIGHT OF CLIMATE CHANGE IN INDIA - ASHKRA*, KRISHNA KUMAR JADAUN; AKRAM AHMAD KHAN (The Journal of Research ANGRAU, 2024)
India is the second-largest producer of wheat in the world. Uttar Pradesh, Punjab, Haryana, Madhya Pradesh, Rajasthan, Bihar, and Gujarat are the major wheat-producing states. Out of all of these states, Uttar Pradesh produces the larger quantity of wheat. Wheat is exported by India to Bangladesh, Sri Lanka, the United Arab Emirates, Yemen, the Philippines, and Indonesia. This study aims to analyze the effects of climate change and other non-climatic factors on wheat production in India between 1991 and 2021. The researcher used climate and non-climate change variables: mean, maximum, minimum temperature, rainfall, production, net MSP, and cultivation area. This work tested long-run cointegration using an Auto-Regressive Distributed Lag (ARDL) bound test cointegration technique to evaluate short-run relationships among modeled variables. CUSUM and CUSUMQ tests assure model reliability and validity. The study’s findings demonstrated that the cultivated area has a major role in enhancing wheat output in the short and long term, while precipitation favors wheat production. In India, a 1% increase in cultivation area can increase 1.3% in wheat production in the long run. In the short run, a 1% increase in cultivation area increased 0.58% wheat production in India. Furthermore, although the temperature has little immediate effect, it is crucial for boosting wheat output over the long term.